Pediatric Primary Orbital Tumors in Dr.M. Djamil General Hospital Padang - Elfi Risalma; Ardizal Rahman (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Introduction : Primary orbital tumors of childhood are different from tumors that occur in adults. Many are congenital with early presentation. In pediatric population, a delay in diagnosis of orbital tumors , even benign tumor can lead to vision loss and deformity. Objective : To report pediatric primary orbital tumors in Dr.M.Djamil Hospital Padang. Method : A retrospective study of orbital tumors in pediatric patients admitted to DR.M.Djamil Hospital between 2003- 2016. Data were obtained from medical records which described patients characteristics based on type, sex,presentation, and management. Result : There were 36 patients of pediatric primary orbital tumors which consist of 20 boys and 16 girls, diagnosis based onclinical sympoms, CT-Scan and pathological examination. The most common tumors in pediatric was Rhabdomyosarcoma in 11 patients (30,55%), Glioma of the Optic nerve in 8 patients (22.22%), Limphoma Malignum in 5 patients (13.88%), Capillary Hemangiomas in 2 patients (5.55%), Cavernous Hemangioma in 2 patients (5.55%), AV Malformation in 2 patients (5.55%), Meningioma in 1 patient (2.77%), Neurofibromatosis in 1 patient (2.77%), Neurilemomoa in 1 patient (2.77%), Limfohemangioma in 1 patient (2.77%), osteoma in 1 patient (2.77%) and Adenoid Cystic Carcinoma in 1 patient (2,94%). Surgery had been performed in 11 patients (30.55%), chemotherapy in 7 patients (19.44%), radiotherapy in 1 patient (2,77%), Combination therapy in 2 patient (5.55%), medical therapy in 1 patient (2.77%) and the remains 14 patients (38.89%) were observed. Conclusion : There were 36 cases pediatric orbital tumors during 14 years. The most common tumor was Rhabdomyosarcoma. Management of pediatric orbital tumors consists of surgery, chemotherapy, radiotherapy and combination therapy.